2012
DOI: 10.1016/j.atherosclerosis.2011.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Objectively-measured and self-reported physical activity and fitness in relation to inflammatory markers in European adolescents: The HELENA Study

Abstract: High PA in adolescence may play an indirect role on lessening low-grade inflammation through improvements in fitness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
2
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(94 citation statements)
references
References 31 publications
7
81
2
4
Order By: Relevance
“…Since our analysis controlled for pubertal stage, we are confident that this apparent protective effect of muscular fitness upon cardiometabolic risk is a result of participating in muscle strengthening activities rather than a consequence of maturation. As seen in other studies Martinez-Gomez et al, 2011), we found that CRF appeared to be more strongly related to cardiometabolic risk in comparison to muscular fitness which may suggest that CRF is more important than muscular fitness in predicting cardiometabolic risk at least during adolescence. Nonetheless, future work that considers implementing prospective and intervention study designs are needed to determine the independent influence of muscular fitness and CRF upon cardiometabolic disease risk in adolescents.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Since our analysis controlled for pubertal stage, we are confident that this apparent protective effect of muscular fitness upon cardiometabolic risk is a result of participating in muscle strengthening activities rather than a consequence of maturation. As seen in other studies Martinez-Gomez et al, 2011), we found that CRF appeared to be more strongly related to cardiometabolic risk in comparison to muscular fitness which may suggest that CRF is more important than muscular fitness in predicting cardiometabolic risk at least during adolescence. Nonetheless, future work that considers implementing prospective and intervention study designs are needed to determine the independent influence of muscular fitness and CRF upon cardiometabolic disease risk in adolescents.…”
Section: Discussionsupporting
confidence: 87%
“…Unlike the study by Anderseen and colleagues, others Martinez-Gomez et al, 2011;Steene-Johannessen et al, 2009) have also examined the relationship between CRF and cardiometabolic risk whilst controlling for muscular fitness. Collectively these authors have demonstrated that CRF was associated with cardiometabolic risk, independent of muscular fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, despite a growing number of studies that analyzes the action and effectiveness of the PA and exercise on cardiometabolic markers in obese adolescents [9][10][11][12]14,15 . Also, there are few studies of systematic review describing intervention procedures with PA in cardiometabolic markers and risk factors of CVD in adolescents.…”
Section: Resumo O Acúmulo De Gordura Corporal é Um Dos Principais Fatmentioning
confidence: 99%
“…Results have pointed to specific therapeutic strategies CVD prevention development at early age 10 . Healthy behavior such as PA, decrease of sedentary behavior and nutritional education may can diminish the concentration of inflammatory cytokines and / or increasing anti-inflammatory cytokines in adolescents 8,11,12 . The increase in glucose uptake and insulin sensitivity in muscle can be stimulated by PA level increasing 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Ces adolescents actifs qui ont une bonne endurance cardiorespiratoire (Figure 4), ont également les scores d'inflammation les plus faibles [20]. Ainsi, les adolescents actifs ont une meilleure condition physique ( Figures 4 et 5 : endurance cardiorespiratoire et force des membres supérieurs) qui est corrélée à des facteurs favorables de bonne santé comme la diminution de l'inflammation [7,[21][22][23], de l'insulinorésistance [18] et de la graisse abdominale [24].…”
Section: Influence Des Conditions De Vieunclassified